GAME EDUKASI PENGENALAN PROFESI SEBAGAI MEDIA PEMBELAJARAN UNTUK ANAK BERBASIS ANDROID - Sri Eka (Inovasi Pembangunan : Jurnal Kelitbangan, 2019)
Abstract: Profession is a form of work that requires the culprit to have certain knowledge obtained through formal education and certain skills gained through work experience in people who first mastered these skills, and continue to renew their skills in accordance with technological development. By introducing the profession to children will help teach children to better appreciate one’s profession, so that children will have the nature of mutual respect and do not look down on one’s profession. Professional introduction will be easier to learn through game education with an attractive and fun appearance. Data collection techniques used in this study are using interviews, literature review, documentation and questionnaires. The source of data / subjects are 20 Qonita Bandar Lampung kindergarten children. The testing method used is the Functionality and Usability aspects. Professional introduction educational game application using MDLC (Multimedia Development Life Cycle) method used is Construct 2 which runs on Android. The results of ISO 9126 testing quality of educational game applications for the introduction of the human profession are obtained values ​​from the aspects of functionality and usability, the results of testing for functionalities namely the game shows that functions in the educational game for the introduction of this profession can run correctly and the results of data processing in the usability test states that the distribution of data has been normally distributed and educational games for professional development can be used as learning variables and can increase children’s interest in learning about the profession from the questionnaire statements that have been filled with Qonita Bandar Lampung kindergarten children. Keywords: Android, Game Edukasi,Profesi,Fungsionality, Usability, Construct.